PENYELENGGARAAN PENYULUHAN PERTANIAN DI PROVINSI MALUKU - Kaliky, Rahima; Hariyadi, Sunamr Samsi; Wastutiningsih, Sri Peny; Priyotamtomo, P. Wiryono (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2011)
The objectives of the research to examine the characteristics of agricultural extension workers and its relation to the implementation of agricultural extension in the province of Moluccas. The study was conducted by survey method in the city of Ambon, Central Moluccas district, and district of West Seram. Determination of the location by a simple random method. Study sample are agricultural extension workers civil servants and THL-TBPP taken as many as 80 people with similar methods. The results showed the level of agricultural extension workers education in the Moluccas is still dominated by high school level. Low levels of education have an impact on the performance of agricultural extension, as seen from the average agriculture extension which make up the programa counseling, only 37% and 52% of that percentage does not integrate with existing agricultural development programs in the area. 46.7% of agricultural extension workers are less able to make a script extension in the form of radio scripts, TV scripts, and print media. In 2010 the agricultural extension workers in the province of Moluccas who can use the Internet only 13.7%.80% of the agricultural extension workers rely on tabloid Sinar Tani as a source of agricultural information technology. To improve the quality and performance of agricultural extension in the region is increasing levels of education and training is an urgent thing.